Improving English Communication Skills of Tourism MSMEs in Derawan Island through Task-Based Language Teaching (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service program addressed the critical need for enhanced English communication skills among tourism Micro, Small, and Medium Enterprises (MSMEs) in Indonesia's 3T (Disadvantaged, Frontier, Outermost) regions, specifically on Derawan Island, East Kalimantan. Despite the island's significant marine tourism potential, local MSMEs face communication barriers with international tourists. Employing a Task-Based Language Teaching (TBLT) approach, the intervention aimed to improve global competitiveness and local economic growth. The methodology involved needs analysis, job-relevant material development, intensive training, and pre-/post-test evaluation. Results showed a 25% average score increase in participants' English proficiency. Qualitatively, 85% reported increased confidence and functional fluency in tourism interactions. A key outcome was the collaborative production of 10 English conversation videos for Derawan Island promotion, 7 of which are actively used on MSME social media. These findings underscore TBLT's effectiveness in empowering local MSMEs with essential communication and digital promotion tools, thus enhancing service quality, expanding market access, and contributing to sustainable economic diversification.